Management of Gout with Individualised Homoeopathy: A Case Report - Jagadabhi, Santosh Kumar; Deshpande, Vishal (Homœopathic Links, 2023)
Gout is a metabolic disorder in which deposition of monosodium urate crystals leading to inflammatory joint disease. The metabolic derangement leading to supersaturation of blood and body fluids with the urate ion to the point of crystal formation is responsible for the presentation. Gout with acute arthritis or chronic arthritis is treated with non-steroidal anti-inflammatory drugs, colchicine, corticosteroids and drugs that lower levels of uric acid in the blood, but these drugs have their impact on different organs of the body. Homoeopathic system of medicine can treat gouty arthritis effectively without any other sequelae. A case of gout in a 52-year-old male patient who presented with severe pain, swelling and tenderness was successfully treated with homoeopathy medicine, Natrum sulph. The medicine prescribed in totality alleviated not only the symptoms of the patient but also lowered the serum uric acid levels to normal.
Keywords: case report; gout; hyperuricemia; individualised homoeopathy; Natrum sulph